2010
DOI: 10.1007/s10519-010-9406-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Candidate Genes on Attention Problems in Children: A Longitudinal Study

Abstract: Attention problems form one of the core characteristics of Attention-Deficit Hyperactive Disorder (ADHD), a multifactorial neurodevelopmental disorder. From twin research it is clear that genes play a considerable role in the etiology and in the stability of ADHD in childhood. Association studies have focused on genes involved in the dopaminergic and serotoninergic systems, but with inconclusive results. This study investigated the effect of 26 Single Nucleotide Polymorphisms (SNPs) in genes encoding for serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These findings suggested that both BDNF polymorphisms could play a role in the etiology of ADHD [269]. From another perspective, van Beijsterveldt et al [270] have developed a parental-assessment report at ages 3, 7, 10, and 12 years over more than 16,000 twin pairs that 1148 genotyped children presenting attention disorder, a cornerstone of ADHD. They developed a longitudinal framework to test genetic association effects with 26 SNPs of genes encoding for several putative contributors to ADHD, including HTR2A, COMT, TPH2, and BDNF.…”
Section: Neurotrophic Factor-regulating Genes In Adhdmentioning
confidence: 99%
“…These findings suggested that both BDNF polymorphisms could play a role in the etiology of ADHD [269]. From another perspective, van Beijsterveldt et al [270] have developed a parental-assessment report at ages 3, 7, 10, and 12 years over more than 16,000 twin pairs that 1148 genotyped children presenting attention disorder, a cornerstone of ADHD. They developed a longitudinal framework to test genetic association effects with 26 SNPs of genes encoding for several putative contributors to ADHD, including HTR2A, COMT, TPH2, and BDNF.…”
Section: Neurotrophic Factor-regulating Genes In Adhdmentioning
confidence: 99%
“…Finally, two studies from a Dutch longitudinal sample assessed from childhood through to adolescence tested whether several serotonin and dopamine system‐related genes, including TPH2 and genes encoding serotonin transporters, were associated with longitudinal measures of attention problems, and anxiety and depression, respectively (Middeldorp, Slof‐Op’t Landt, Medland, van Beijsterveldt, Bartels, Willemsen, Hottenga, de Geus, Suchiman, Dolan, Neale, Slagboom & Boomsma, 2010; van Beijsterveldt, Middeldorp, Slof‐Op’t Landt, Bartels, Hottenga, Suchiman, Slagboom & Boomsma, 2011). Perhaps surprisingly, however, these longitudinal behavioral traits did not show an association with the selected candidate genes.…”
Section: Developmental Candidate Gene Association Studiesmentioning
confidence: 99%
“…Neale et al ( 2000 ) partitioned variation in serum APOE levels into that associated with the APOE locus and residual genetic variance. In a study of attention problems, van Beijsterveldt et al ( 2011 ) incorporated measured candidate gene information on SNPs in the serotonergic, dopaminergic system and the BDNF gene. The effect of SNPs was tested on a latent factor that summarized multiple assessments of attention problems across childhood.…”
Section: Introductionmentioning
confidence: 99%